HUBUNGAN PENGETAHUAN DAN SIKAP IBU TENTANG GIZI SEIMBANG DENGAN POLA MAKAN ANAK USIA 24-59 BULAN DI WILAYAH KERJA PUSKESMAS KOTA MATSUM KECAMATAN MEDAN AREA - Nadya Amelia Harahap; Ernawati Nasution; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The problem of balanced nutrition in Indonesia is still a serious problem. The importance of nutrition for the child's life in order to support its growth and development, the balanced consumption pattern needs to be applied by mother. The purpose of this research was to know the relation of knowledge and attitude of mother about balanced nutrition of children aged 24-59 months in working area of ​​Puskesmas Matsum Kecamatan Medan Area. This research was an analitic research which used multistage random sampling design with total sample of 110 children. Data were collected by using interviews on mothers having children aged 24-59 months using structured questionnaire. Types of food, Food Frequency Questionnaire, and total intake of macro and micro nutrients were seen using 24 hour recall form. The results showed that there is a relationship between knowledge and food pattern of children. This is evidenced by the existence of a significant relationship between knowledge with the type and amount of intake of macro and micro nutrients in children. The p value obtained for the relationship between knowledge with the type and amount of macro and micro nutrients was (p <0.05). Based on the results of the study also shows a relationship between attitude with the child's diet. This is evidenced by the value (p <0.05) which means, there is a significant relationship between the attitude with the type and amount of intake of macro nutrients and micronutrients in children. The food pattern of children aged 24-59 months seen from the consumption of rice every day. The most frequency of side dishes is fish and eggs. Vegetables are often consumed by children such as carrots and mustard also consume ‘kerupuk and ‘chiki’ every day. Suggestions in this study to the Public Health Office and Puskesmas to socialize balanced nutrition through a balanced nutrition handbook for health workers for ‘kader’ to keep voicing about balanced nutrition in the community. Keywords: Knowledge, Attitude, Balanced Nutrition, Food Pattern